British-American Coordination to Overthrow Cheddi Jagan Government in British Guiana1961-1964 - Shattab, Dr. Abdullah Muslim (Thi Qar Arts Journal, 2022)
The research studies the coordination of efforts between the United States and Britain towards the government of President Cheddi Jagan in British Guiana, specifically for the years (1961-1964), as it witnessed clear efforts to thwart and get rid of it by obstructing its efforts with economic reform, and working to delay the realization of its aspirations to obtain independence from British.By not giving them loans or foreign aid to help Guyana's weak economy, or inciting and financing internal strikes, such as trade unions, and among the US-British efforts to bring down the,work to change the electoral system .